2017
DOI: 10.3748/wjg.v23.i21.3900
|View full text |Cite
|
Sign up to set email alerts
|

Role of three-dimensional endoanal ultrasound in assessing the anal sphincter morphology of female patients with chronic proctalgia

Abstract: AIMTo assess the role of three-dimensional endoanal ultrasound (3D-EAUS) for morphological assessment of the anal sphincter of female patients with chronic proctalgia (CP).METHODSIn this unmatched case control study, 30 consecutive female patients with CP and 25 normal women (control group) were enrolled. 3D-EAUS was performed in all subjects. Thickness and length of internal anal sphincter (IAS), thickness of puborectalis muscle (PR), length of the external anal sphincter (EAS) plus PR, and puborectalis angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Our results indicated that biofeedback therapy had better efficacy than acupuncture in patients with pelvic floor dyssynergia, suggesting that this pain may be attributed to the uncoordinated movement of puborectalis muscle. 21 Like biofeedback, acupuncture treatment relieved the pain of patients with FAP and also significantly improved the mental health of these patients. In agreement, a previous study showed that acupuncture at Ganshu (BL18) had analgesic effects due to its influence on the expression of brain-gut peptide substance P (SP), which affects mental states such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that biofeedback therapy had better efficacy than acupuncture in patients with pelvic floor dyssynergia, suggesting that this pain may be attributed to the uncoordinated movement of puborectalis muscle. 21 Like biofeedback, acupuncture treatment relieved the pain of patients with FAP and also significantly improved the mental health of these patients. In agreement, a previous study showed that acupuncture at Ganshu (BL18) had analgesic effects due to its influence on the expression of brain-gut peptide substance P (SP), which affects mental states such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…[10-14] . Xue et al [15] used EDF to study functional anal pain. It was found that abnormal contraction and hypertrophy of puborectalis muscles were the main causes of functional anal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestro trabajo proporciona una colección iconográfica de imágenes seccionales de cadáver, resonancia magnética y ecografía de gran calidad, pudiendo aplicarse a distintas funciones como instruir a los estudiantes en la interpretación de imágenes Es una característica importante de nuestro desarrollo informático la posibilidad de correlacionar dos técnicas de imagen tan importantes en el estudio de la pelvis, especialmente la femenina, como son la RM y la ecografía, ya que son totalmente distintas en cuanto a su obtención y especialmente en su interpretación. Ambos estudios de imagen son fundamentales para el diagnóstico de múltiples patologías pélvicas, así como para la planificación de su tratamiento, como se aprecia en los trabajos de numerosos autores (Chan y Tse, 2018;Graupera et al, 2018;Kaniewska et al, 2018;Kim et al, 2018;Vellucci et al, 2018;Dietz, 2017;Murad-Regadas et al, 2017;Ram et al, 2017;Salsi et al, 2017;Wlaźlak et al, 2017;Xuang et al, 2017;Xue et al, 2017;Peng et al, 2016;Terracciano et al, 2016;Thibault-Gagnon et al, 2016;Portilla et al, 2015;Van Delft et al, 2015;Youssef et al, 2015;Bitti et al, 2014;Dietz, 2014;García del Salto et al, 2014;Hennemann et al, 2014;Morin et al,2014;Murad-Regadas et al, 2014;Nardos et al, 2014;Rostaminia et al, 2014a;Rostaminia et al, 2014b;Dietz et al, 2012), siendo su uso muchas veces conjunto (Chamié et al,2018;Javadian et al, 2017;Vergeldt et al, 2016;Notten et al, 2014). La mayoría de los estudiantes se sienten intimidados la primera vez...…”
Section: Bones3dandhl=es_419)unclassified